Analisis Faktor yang Mempengaruhi Partisipasi Perempuan dalam Ekonomi Lokal di Daerah Tertinggal - Anisa Rahmawati Dewi; Reza Fadhil Akbar; Nur Aini Salma (Economics Note, 2025)
This study aims to analyze the factors influencing women’s participation in the local economy in underdeveloped regions. As a group with significant potential to drive economic growth, women often face challenges in actively participating in economic sectors, particularly in areas with limited infrastructure and access. Factors such as education, culture, access to economic resources, and government policies play a significant role in shaping the level of women’s participation. This research employs a quantitative approach through surveys conducted among women engaged in economic activities in several underdeveloped regions of Indonesia. The findings indicate that educational attainment, family support, and the availability of economic empowerment programs are the dominant factors that enhance women’s participation. Conversely, conservative cultural norms and limited access to business capital constitute the main obstacles. Therefore, more inclusive policies are needed to address these barriers and to encourage women in underdeveloped areas to become more active in the local economy. This study provides recommendations for the government and relevant stakeholders in designing programs that support women’s economic empowerment.